SIMULASI KUNCI ELEKTRONIK DENGAN ENKRIPSI MELALUI BLUETOOTH PADA PONSEL - Neforawati, Indri; Saragih, Hoga (CommIT (Communication and Information Technology) Journal, 2008)
Currently the facility provided by mobile phones is very diverse. Starting from the phone, SMS, camera, music player, all rolled into one. Obviously the phone can also be used as electronic keys to replace the existing analog key at this time. Usually, to open a door key one must use a key, so to access a lot of doors must have a lot of different keys. But if the phone is used as an electronic key access control must implement all the keys are not needed anymore, just with one phone can open many locks. Simulation of an electronic lock is designed to use the phone as a remote control, and the computer as a central controller. Communication between mobile phones and computers using Bluetooth. While functioning as a door lock which is connected via parallel port of computer. This electronic key system to apply Access Control using RC4 encryption and MD5 Hashing. Design modules are built using NetBeans IDE 4.1 and the MySQL database, with some additional libraries. Libraries that are mobility netbeans 4.1, mysql-connector-java-3.0.9, BlueCove, Bluelet-Benhui. Phones that use must support the Java MIDP 2.0 and JSR-82.Keywords: Hashing MD5, Enkripsi RC4, NetBeans IDE 4.1, mysql-connector-java-3.0.9